2022-RA-274-ESGO Prehabilitation to improve outcomes of patients with gynaecological cancer: a new window of opportunity?. (20th October 2022) - Keidan, Nathaniel; Dhanis, Joëlle; Blake, Dominic; Strijker, Dieuwke; Rundle, Stuart; Ham, Maaike van; Pijnenborg, Hanny; Smits, Anke
Abstract : Introduction/Background: Prehabilitation programmes aim to optimise the period between cancer diagnosis and treatment, by enhancing an individual's functional and mental capacity prior to surgery. The aim of this study was to review the literature evaluating the effect of prehabilitation programmes on postoperative outcomes and quality of life of patients with gynaecological cancer undergoing surgery. Methodology: This was a systematic review, performed according to Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. Databases including Pubmed, Medline, EMBASE (Ovid) and PsycINFO were systematically searched to identify studies evaluating the effect of prehabilitation programmes on patients with gynaecological cancer. Both unimodal and multimodal prehabilitation programmes were included encompassing physical exercise, nutritional and psychological support. Primary outcomes were operative complications and quality of life. Secondary outcomes were anthropometrics and adherence to the programme. Results: Seven studies fulfilled the inclusion criteria, comprising 580 patients. Included studies comprised non-randomised prospective studies (n=4), retrospective studies (n=2) and one case report. Unimodal programmes and multimodal programmes were included. In patients with ovarian cancer, multimodal prehabilitation resulted in significantly reduced hospital stay and time to chemotherapy. In patients with endometrial and cervical cancer, prehabilitation was associated with significant weight loss, but no significant effects on operative complications or mortality. No adverse events of the programmes were reported. Conclusion: Evidence on the effect of prehabilitation for patients with gynaecological cancer is limited. Future studies are needed to determine the effects on postoperative complications and quality of life.